Bule Barbie’s YouTube Channel and Religious Commodification: A Multimodal Discourse Analysis - Theresya, Pingky; Mahendra, Radya Rakha; Arafat, Salsabila Benj; Syahriyani, Alfi (UIN Syarif Hidayatullah Jakarta, 2025)
Commodification refers to the process of something that is given a market value and traded. Various aspects of life can be commodified, including religion. This study investigates how Bule Barbie’s YouTube content represents the commodification of Islam by employing Multimodal Discourse Analysis (MDA), as proposed by Gunther Kress and Theo van Leeuwen, along with Karl Marx’s theory of commodification. This research aims to explore how religious elements are transformed into commodities on social media platforms, particularly YouTube. The analysis focuses on five multimodal systems: linguistic, visual, audio, gestural, and spatial. Bule Barbie's videos are deliberately presented engagingly and cheerfully to attract viewers, reflected in her friendly persona. The findings reveal that the commodification process can be observed through the use of Islamic expressions such as Alhamdulillah, Bismillahirrahmanirrahim, and Allahu Akbar; the mention of Islamic practices such as fasting, takjil, and Eid al-Fitr; her use of religious attires such as gamis and hijab; and her visits to mosques. These elements show how all five multimodal systems are utilized to convey and commodify Islamic values in the content. The implication of this research is to raise awareness about how religious symbols and practices can be commercialized in digital media, prompting further discussion on the ethical boundaries of spiritual representation in online content.